Fresno County Women Lawyers/Fresno County Bar Association Seminar on Judicial Selection Held at Ramada Inn - Watkins, Howard::::::::: (1989)
Los Angeles Judge Judith Chirlin, Fresno attorney Julia Ann Brungess and speaker Melinda Vaughn seated at table